IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DALAM PEMBELAJARAN IPS DI SMP KARANGTURI SEMARANG (Universitas Negeri Semarang, 2023)
Multicultural education is education related to social justice, democracy, and human rights in a plural society. Karangturi Junior High School Semarang is a school that has ethnic, cultural, and religious. The method used in this research is qualitative with a case study approach. The results of this study are (1) the implementation of multicultural education in social studies learning is carried out through planning such as integrating multicultural values in the learning implementation plan (RPP), in the implementation through the development of diversity paradigms such as giving positive values, inculcating a tolerant attitude, next also accustomed to accepting differences through group discussions and presentations. learning process. (2) The supporting factors for the implementation of multicultural education include school status, school environment, school vision and mission, extracurricular programs, the right approach, adequate facilities and infrastructure. The obstacle is about the material which does’t all contain diversity, the absence of an evaluation instrument for multicultural attitudes. Pendidikan multikultural merupakan pendidikan yang terkait dengan keadilan sosial, demokrasi, dan hak asasi manusia di tengah masyarakat plural. SMP Karangturi Semarang merupakan sekolah yang memiliki keberagaman etnik, budaya, dan agama. Metode yang digunakan dalam penelitian ini yaitu kualitatif dengan pendekatan studi kasus. Hasil penelitian ini adalah (1) implementasi pendidikan multikultural dalam pembelajaran IPS di laksanakan melalui perencanaan seperti mengintegrasikan nilai-nilai multikultural dalam rencana pelaksanaan pembelajaran(RPP), pada pelaksanaan melalui pembangunan paradigma keberagaman seperti pemberian nilai-nilai positif, penanaman sikap toleran. kemudian peserta didik juga dibiasakan menerima perbedaan melalui diskusi maupun presentasi kelompok. (2) Faktor-faktor pendukung implementasi pendidikan multikultural antara lain status sekolah, lingkungan sekolah, visi misi sekolah, program ekstrakulikuler, pendekatan yang tepat, sarana dan prasarana yang memadai. Hambatannya adalah perihal materi yang tidak semuanya mengandung keberagaman tidak adanya instrumen evaluasi sikap multikultural, dan kurang meratanya kebeberagaman antar kelas.